UNDERSTANDING FACTORS THAT INFLUENCE HOUSE PURCHASE INTENTION AMONG CONSUMERS IN KOTA KINABALU : AN APPLICATION OF BUYER BEHAVIOR MODEL THEORY - Chia, Julius; Harun, Amran; Mohd Kassim, Abdul Wahid; Martin, David; Kepal, Noreina (Journal of Technology Management and Business, 2016)
Houses made ready by housing developers in Sabah are solely based on economic factors as oppose to consumers preferences and interest. A better understanding of factors contributing to decision-making of buyers in real estate markets would be beneficial to both buyers and housing industry. Therefore, this study aims to understand consumer behaviour towards house purchase using The Theory of Buyer Behaviour Model (Perceptual and Output). The perceptual constructs consist of housing attributes such as house features, living space, distance and environment. The output construct refers to house purchase intention. Exogenous variables of the model are superstition-numbers, superstition-ghosts, developer brand and financing. The objective of this study is to examine the influence of housing attributes on house purchase intention. Based on 235 working adult respondents, findings indicated that house features, financing, distance, environment and superstition-numbers have significant positive relationships with house purchase intention. In addition, implications of the studies for several stakeholders are also discussed.Keywords: Housing Attributes, Theory of Buyer Behavior Model, House Purchase Intention, Sabah